Productivity Improvement Strategy Through Participatory Approach, Digital Marketing, and Occupational Safety in Knife Craftsmen Groups in Sukawati Village, Gianyar - A A I Krisna Gangga DEWI; Ni Pitu Ayu Tika KURNIAWATI; Anastacia Patricia Novlina NURAK; Ni Putu ARTINI; A A Esti Widya ISWARI (PT Keberlanjutan Strategis Indonesia, 2025)
The Swandya Prapen knife craftsmen group in Sukawati Village plays a significant role in the local home industry sector but faces challenges in marketing, occupational safety, and productivity. This community service program aimed to empower the craftsmen group by implementing digital marketing strategies, providing occupational health and safety (OHS) training, and utilizing a participatory approach to enhance their productivity. Activities included hands-on training, technical guidance, and collaborative evaluation based on the group’s specific needs. The program successfully increased the craftsmen’s ability to promote their knives through digital platforms, improved workplace safety practices, and fostered stronger teamwork within the group. As a result, the productivity and market competitiveness of the Swandya Prapen knife craftsmen improved significantly. In addition, the artisans became more aware of the importance of adopting personal protective equipment and maintaining a safe workspace to sustain their long-term health and performance. The participatory approach also encouraged more active involvement of members in decision-making, strengthening ownership and commitment to shared goals. This initiative highlights the effectiveness of combining digital tools, safety measures, and participatory methods in advancing the sustainability and growth of traditional knife-making communities while simultaneously preserving cultural heritage and empowering local economies.